Incidence of cephalosporin‐induced anaphylaxis and clinical efficacy of screening intradermal tests with cephalosporins: A large multicenter retrospective cohort study. Issue 9 (30th August 2018) - Yang, M.‐S.; Kang, D.Y.; Seo, B.; Park, H. J.; Park, S.‐Y.; Kim, M.‐Y.; Park, K. H.; Koo, S.‐M.; Nam, Y.‐H.; Kim, S.; Jung, J.‐W.; Kim, T.‐B.; et al.
Abstract: Background: Few studies have investigated the incidence of anaphylaxis induced by individual or structurally similar cephalosporins. The aims of the study were to assess the incidence of cephalosporin‐induced anaphylaxis and evaluate the clinical efficacy of screening skin tests. Methods: In this retrospective cohort study, we obtained information on total cephalosporin use and cephalosporin‐induced anaphylaxis in intravenous cephalosporin recipients in 12 general hospitals between 2013 and 2015. Cephalosporins were divided into 4 groups according to similar side‐chain structures. The incidence of cephalosporin‐induced anaphylaxis was assessed for each cephalosporin, cephalosporin generation, and side‐chain group. To verify the efficacy of screening intradermal tests (IDT) with cephalosporin, the 12 hospitals were assigned to the intervention or control group depending on whether they performed screening IDT before the administration of cephalosporins. Results: We identified 76 cases of cephalosporin‐induced anaphylaxis with 1 123 345 exposures to intravenous cephalosporins (6.8 per 100 000 exposures), and the incidence of fatal anaphylaxis by cephalosporin was 0.1 cases per 100 000 exposures. The highest incidences of anaphylaxis occurred in the ceftizoxime (13.0 cases per 100 000 exposures) and side‐chain group 1 (cefepime, cefotaxime, ceftizoxime, ceftriaxone, and cefuroxime; 9.3 per 100 000). There was no case of anaphylaxis induced by cefoxitin, cefmetazole, cefminox, and cefotiam. The clinical effectiveness of routine screening IDT was not significant ( P  = .06). Conclusions: The incidence of cephalosporin‐induced anaphylaxis differed according to individual drugs and side‐chain structure. Screening IDT showed no clinical efficacy at a population level. Abstract : Among total 1 140 354 cephalosporin treatment courses from 12 hours hospitals, the incidence of cephalosporin induced anaphylaxis was 6.8 per 100 000 exposures and the related fatality was 1.3%. The incidence of cephalosporin induced anaphylaxis varies with each drug type, and the highest incidences of anaphylaxis occurred in the ceftizoxime (13.0 cases per 100 000 exposures). Screening intradermal tests with cephalosporin failed to show preventive effect on cephalosporin‐induced anaphylaxis.